TACTICAL AND STATISTICAL ANALYSIS OF THE GAME STRATEGIES OF LEADING VOLLEYBALL TEAMS IN THE MODERN COMPETITIVE PROCESS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the tactical and statistical foundations of the game strategies used by leading volleyball teams in the modern competitive process. Contemporary volleyball is characterized by high game intensity, rapid tactical variation, and the growing importance of performance analytics in decision-making. Under such conditions, the effectiveness of a team depends not only on the technical skill of players, but also on the rational organization of offensive and defensive systems, the stability of tactical interactions, and the ability to adapt game models to the dynamics of the match. The study focuses on the analysis of key tactical indicators and statistical parameters that determine the competitive success of high-level volleyball teams. Particular attention is given to serve efficiency, attack organization, block performance, reception stability, transition speed, error structure, and tactical distribution of actions in different phases of play. The article argues that tactical-statistical analysis makes it possible to identify stable patterns in team behavior, evaluate the effectiveness of game strategies, and reveal the structural features that distinguish leading teams from less successful opponents. The findings support the view that the integration of statistical data with tactical interpretation improves the scientific understanding of competitive activity and creates broader methodological opportunities for coaching, training design, and the preparation of future specialists in physical education and sports.
Keywords: Volleyball, game strategies, tactical analysis, statistical analysis, competitive process, team performance, offensive systems, defensive systems, serve efficiency, attack organization, block performance, match analytics.